Walther TP Kal. 6.35 und .22 l.r. (Carl Walther Sportswaffenfabrik Ulm/Donau, 1961)
"At the end of WWII, when founded a new factory in Ulm, Germany, Walther started thinking about the production of a new vest pocket pistol for the civilian market. The design of the Model TP (Taschenpistole or pocket pistol) is more or less the same as the very successful Modell 9. The TP was introduced in 1961 (continued in production untill 1971) as the first Walther vest pocket pistol of the post WWII era and was produced in a .25 ACP and a .22 lr version. There are two minor variants of the .25 ACP models known. The early model [ the model described in this technical paper] has the Walther-banner on the left side of the slide and the inscription in sans-serif characters 'Modell TP Cal. 6,35mm.' The right side of the slide is inscribed "Carl Walther Waffenfabrik Ulm/Do."-- https://unblinkingeye.com/Guns/WTP/wtp.html